Wheat productivity and nitrogen use efficiency in no-till systems: a comparative analysis of crop-pasture and continuous cropping rotations in Uruguay - Mori Alvez, Cristina; Ernst Benech, Oswaldo; González Barrios, Pablo; Perdomo Varela, Carlos (Frontiers in Sustainable Food Systems, 2024)
IntroductionUruguayan agriculture’s transition to no-till farming and intensified practices, replacing crop-pasture (CP) systems with continuous cropping (CC) rotations, has disrupted biological nitrogen fixation (BNF). Despite this, diversified cropping sequences, including C4 species, have maintained the soil organic carbon (SOC) balance under no-till management, with limited overall impacts on productivity and sustainability. The effects of these changes on wheat productivity and nitrogen use efficiency (NUE) need to be further investigated.MethodsThis study, conducted within a long-term experiment (LTE) under rainfed conditions, compared wheat productivity in CP and CC rotations. Wheat following CP and CC were analyzed over three seasons. Variables measured included soil nitrogen (N) concentration, wheat grain yield (WGY), grain protein concentration (GPC), and NUE. Four N fertilizer levels were applied to each rotation system to assess their impact.ResultsCC rotation consistently outperformed CP in WGY, with 2425 and 1668 kg ha−1 averages, respectively. CP showed slightly higher GPC (10.92%) than CC (10.48%). Nitrate-N levels at tillering positively correlated with WGY and negatively with GPC, but the relationship differed by rotation. Soil NUE indices were higher in CC rotations.DiscussionThe study’s findings highlighted the potential of CC rotation, especially when including C4 species in the crop sequence, to achieve higher wheat productivity in the short term due to healthier soil conditions compared to wheat seeded after post-pasture in CP. Additionally, our study highlights that the effect of the previous crop on yield and NUE in wheat was more relevant than the expected residual effect of the pasture phase in CP, primarily due to the quality of residues and the temporary adverse effects of soil compaction caused by livestock trampling.